2001
DOI: 10.1046/j.1360-0443.2001.9679877.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and binge drinking in Novosibirsk, Russia, 1985–95

Abstract: Alcohol consumption and prevalence of binge drinking were high in men and low in women. The frequency of binge drinking among men increased between 1985/86 and 1988/89 and remained stable between 1988/89 and 1994/95. This is not consistent with trends in mortality. Shorter-term fluctuations between surveys, however, cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 0 publications
5
46
0
Order By: Relevance
“…Most studies report much heavier and more prevalent alcohol consumption in men compared with women. For instance, in Russia and Ukraine, the rates of monthly heavy episodic or heavy alcohol use vary from 31% to 82% for men and from 1% to 11% for women (Bobak et al, 1999(Bobak et al, , 2004Malyutina et al, 2001;Pakriev et al, 1998;Webb et al, 2005). Two recent surveys conducted in Russia estimated the prevalence of any alcohol consumption among pregnant women to be as high as 25.5%-60%; however, results should be generalized with caution (Grjibovski et al, 2002;Kristjanson et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Most studies report much heavier and more prevalent alcohol consumption in men compared with women. For instance, in Russia and Ukraine, the rates of monthly heavy episodic or heavy alcohol use vary from 31% to 82% for men and from 1% to 11% for women (Bobak et al, 1999(Bobak et al, , 2004Malyutina et al, 2001;Pakriev et al, 1998;Webb et al, 2005). Two recent surveys conducted in Russia estimated the prevalence of any alcohol consumption among pregnant women to be as high as 25.5%-60%; however, results should be generalized with caution (Grjibovski et al, 2002;Kristjanson et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies in Russia also found infrequent drinking but high intake per occasion in men and relatively low consumption in women. [22][23][24][25] Our ecological and individual level analyses show that the mean dose per session accounted for a substantial part of the differences in alcohol related problem in men in the three countries. These findings support the hypothesis that drinking pattern may potentiate the negative role of alcohol in Russia.…”
Section: Discussionmentioning
confidence: 99%
“…Concern about the adverse effects of alcohol on health and other outcomes led the then-President Mikhail Gorbachev to institute an antialcohol campaign in 1985. Alcohol consumption, which initially decreased during the campaign, increased significantly after the campaign ended in 1987 (Malyutina et al, 2001;Nemtsov, 2000Nemtsov, , 2005. Malyutina et al (2001) reported that abstinence rates among women declined from 52 to 8% between 19858% between and 19958% between .…”
Section: H Istorically Alcohol Consumption Inmentioning
confidence: 95%
“…Alcohol consumption, which initially decreased during the campaign, increased significantly after the campaign ended in 1987 (Malyutina et al, 2001;Nemtsov, 2000Nemtsov, , 2005. Malyutina et al (2001) reported that abstinence rates among women declined from 52 to 8% between 19858% between and 19958% between . Bobak et al (1999 found that 35% of Russian women in a 1996 survey reported being abstainers.…”
Section: H Istorically Alcohol Consumption Inmentioning
confidence: 95%
See 1 more Smart Citation